EKSTRAKSI DAN FRAKSINASI BUAH PISANG MENTAH (Musa paradisiaca L.) - Ivan Charles S. Klau; Arista Wahyu Ningsih; Waldo Farel Irvana Putra (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2022)
Indonesia is a country rich in natural plants. And many of these plants also produce fruit. One of these plants is banana. Lots of Indonesian people consume bananas. Bananas have many benefits. The content of secondary metabolites in fruit flesh, fruit peel and banana raw fruit is different, so that their pharmacological activities are also different. Therefore, the purpose of this study was to determine the comparison of simplicia yield, extract and fraction of simplicia peel, fruit flesh and unripe bananas. The difference in yield produced will give a difference in the content of the secondary metabolites. The methods used are the manufacture of simplicia powder, the manufacture of vegetable extracts by maceration, fractionation by the liquid-liquid method. The results obtained from the manufacture of simplicia obtained good results because it has a water content in accordance with quality standards, which is less than 10%. The results showed that the average drying loss of simplicia pulp was 34%, raw fruit was 22% and fruit skin was 13%. Then in the extraction process, the highest percentage yield of the thick extract in the fruit was 9%. In the fractionation process, the largest fraction was obtained from the ethyl acetate fraction which is 34% for the skin of the unripe fruit and 39% for the flesh of the unripe fruit.